An important role of temperature dependent scattering time in understanding the high temperature thermoelectric behavior of strongly correlated system: La0.75Ba0.25CoO3. (31st January 2017) - Singh, Saurabh; Kumar, Devendra; Pandey, Sudhir K
Abstract: In the present work, we report the temperature dependent thermopower ( α ) behavior of La0.75 Ba0.25 CoO3 compound in the temperature range 300–600 K. Using the Heikes formula, the estimated value of α corresponding to high-spin configuration of Co 3+ and Co 4+ ions is found to be ̃16 μ V K − 1, which is close to the experimental value, ̃13 μ V K − 1, observed at ̃600 K. The temperature dependent TE behavior of the compound is studied by combining the WIEN2K and BoltzTrap code. The self consistency field calculations show that the compound have ferromagnetic ground state structure. The electronic structure calculations give half metallic characteristic with a small gap of ̃50 meV for down spin channel. The large and positive value for down spin channel is obtained due to the unique band structure shown by this spin channel. The temperature dependent relaxation time for both the spin-channel charge carriers is considered to study the thermopower data in temperature range 300–600 K. For evaluation of α, almost linear values of τ u p and a non-linear values of τ d n are taken into account. By taking the temperature dependent values of relaxation time for both the spin channels, the calculated values of α using two current model are found to be in good agreement with experimental values in the temperature range 300–600 K. At 300 K, the calculated value of electrical conductivity by using the same value of relaxation time, i.e. 0.1 × 10 −14 seconds for spin-up and 0.66 × 10 − 14 seconds for spin-dn channel, is found to be equal to the experimentally reported value.